EXISTENCE OF SUFISM IN THE MIDST OF MULTICULTURAL AND GLOBAL COMMUNITIES (Prospects and Problems of the Development) - Ahmad Suradi; Nurfitria Dewi (Jurnal Ushuluddin, 2019)
This article aims to examine the prospects and problems of developing Sufism in the multicultural and globalization era. This research is a library research. In the era of multiculturalism and globalization that civilization, science and technology have influenced all aspects of life, including the touch of spiritual values. In this case, ideally, science and technology in Islam must be able to deliver someone to further increase the faith and piety to Allah. The advancement of science in this multicultural and global era must be useful to recognize the creation, majesty and greatness of God, so that it can encourage people to get closer to Him. But in reality, modernization only satisfies the outer needs, even though humans will remain nervous as long as their inner and divine needs are not fulfilled. It is hoped that the values of Sufism, which is spiritual conditioning, can fill the emptiness of the human soul so that the obedience of the people in carrying out the rules of Shari’a and the appreciation of religion at the level of essence and Sufism does not slip into the abyss of shirk and khurafat